SISTEM INFORMASI GEOGRAFIS PAPAN REKLAME (BILLBOARD) di KOTA DENPASAR BERBASIS WEB MENGGUNAKAN LEAFLET JAVASCRIPT: SISTEM INFORMASI GEOGRAFIS - Iwan Setiawan Gde; Putu Roy Nurbhawa (Jurnal Manajemen dan Teknologi Informasi, 2021)
Abstract Advertisements are objects, tools, actions or media which according to their commercial purpose, are used to introduce goods and services. The problem that is often faced by the tenants is determining the location of the point where the billboard is still empty, because the tenants have so far had to do a direct survey, considering the location of the billboard points which are very large and numerous. The research methodology is carried out using the waterfall method, by presenting it as different process phases such as requirements analysis and definition, software design, implementation and unit testing, system integration and testing, operation and maintenance, by adding a JavaScript Leaflet or in short (LaefletJS) , Leaflet allows anyone without a GIS (geographic Information System) background to display a web map tile on a public server with ease. With this Geographical information system, it can help the Denpasar city government to monitor billboards. Vendors and advertisers can also monitor billboards that have an active or inactive status, because the system created is supported by spatial data in the form of a map that functions to display billboard points along with billboard status information.